Ivan’s Immortality: Christian Apologetics, Dostoevsky, and the Metaphysics of War - Harris, Joshua (The international journal of religion and spirituality in society, 2013)
Fyodor Dostoevsky writes in his masterpiece, The Brothers Karamazov: "There is no virtue if there is no immortality." Many Christian apologists, reacting against contemporary secularism’s challenge to the existence of God, use this quote as support for an objective, systematized morality. William Lane Craig, Dinesh D’Souza, Douglas Wilson, and others have referred to it in this context on the public stage, and the datum all but totalizes their respective projects of thought, at least in terms of ethics. But while the Platonically informed argument offers an easily identifiable, propositional account of morality, a serious consideration of Mikhail Bakhtin’s characterization of the text as polyphonic seems to undermine this reading of Dostoevsky. Using the language of the "Other" in Levinas’ Totality and Infinity, it is possible to render a meaning of this line as almost precisely the opposite of the aforementioned conclusion. Far from positing a Platonic form of "virtue" by which human acts are compared and therefore totalized, Dostoevsky’s immortality should be received as the infinite excess of the Other—a sort of deconstruction of any such attempt at totalization. This reading offers a much more faithful response to the the complexity of the novel and, in turn, Christian morality overall.